COMPARISON OF ILLEGAL-UNREPORTED-UNREGULATED FISHING PRACTICES BASED ON PORT TYPE IN JAKARTA BAY - Ayi Ardisastra; Yossa Istiadi; Umar Mansyur (Universitas Pakuan, 2022)
An assessment on Comparison of Illegal-Unreported-Unregulated (IUU) Fishing practices based on type of port in Jakarta Bay conducted on 8-12 February 2021 in 2 (two) classes of fishing port namely PPS (Pelabuhan Perikanan Samudra) Nizam Zachman and PPN (Pelabuhan Perikanan Nusantara) Muara Angke. IUU Fishing violation practices is a fishing activity that is inconsistent and not in accordance with the conservation values and fisheries management, and violates international, regional, and national policies. Indonesia’s losses due to the practice of IUU fishing reach IDR 300 trillion annually or about 25% of Indonesia's total fishery potential. Aims of the assessment are to identify a violation rate of IUU Fishing, determine the value of IUU Fishing index and strategy for prevention and eradication of IUU Fishing practices in Jakarta Bay fishing port. Add the methods/analyse here … As a result of the studies showed that the highest of IUU Fishing violation rate occured at PPN Muara Angke which were about 184 of vessels compare with PPS Nizam Zachman which were only 63 vessels that contravene with rules. In addition, according to the index values of IUU Fishing at both fishing ports were moderate namely about 2,03 for PPS Nizam Zachman and 1,77 for PPN Muara Angke. Furthermore, based on the result of SWOT analysis that there are 3 (three) strategies to prevent and eradicate IUU Fishing practices consisted of: i) the strategy of optimization of integrated services which has a weight value of about 33,5%; ii) the strategy of establishment of law enforcement institution forum which has a weight value of about 31,3%; iii) the strategy of administration sanction for offender of unreported fishing which has a weight value of about 20,3%; and iv) the strategy of strengthening of vessels owner or patron (collectors) which has a weight value of about 15,0%